1993
DOI: 10.1111/j.1600-0765.1993.tb02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a 21‐day, partial‐mouth gingivitis model for evaluating chemotherapeutic dentifrices

Abstract: The experimental gingivitis model has long been used to evaluate chemotherapeutic agents in mouthrinses. Only recently however has the model been modified to test undiluted dentifrices by using a toothshield both to apply dentifrice and to protect selected teeth from toothbrushing. This also enables participants to brush the rest of the mouth and avoid the unpleasantness of 3 weeks without oral hygiene. Because of its well-documented efficacy, chlorhexidine was used in a toothpaste formulation to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
2
23
0
1
Order By: Relevance
“…This modification made the model easier to accept by the prospective participants, therefore more feasible from a practical perspective. Consistent with previous studies where a toothshield was used (Putt et al 1993, Preshaw et al 2001, plaque accumulation did not seem to be impaired by the use of a stent. Previous reports included use of two quadrants (Deinzer et al 1999), one quadrant (Putt et al 1993, van der Weijen et al 1994a, and any number of contiguous teeth (Bosman & Powell 1977, Matheny et al 1993, Daly & Highfield 1996, extending over one (Bosman & Powell 1977, Daly & Highfield 1996 or two quadrants (Matheny et al 1993).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This modification made the model easier to accept by the prospective participants, therefore more feasible from a practical perspective. Consistent with previous studies where a toothshield was used (Putt et al 1993, Preshaw et al 2001, plaque accumulation did not seem to be impaired by the use of a stent. Previous reports included use of two quadrants (Deinzer et al 1999), one quadrant (Putt et al 1993, van der Weijen et al 1994a, and any number of contiguous teeth (Bosman & Powell 1977, Matheny et al 1993, Daly & Highfield 1996, extending over one (Bosman & Powell 1977, Daly & Highfield 1996 or two quadrants (Matheny et al 1993).…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports included use of two quadrants (Deinzer et al 1999), one quadrant (Putt et al 1993, van der Weijen et al 1994a, and any number of contiguous teeth (Bosman & Powell 1977, Matheny et al 1993, Daly & Highfield 1996, extending over one (Bosman & Powell 1977, Daly & Highfield 1996 or two quadrants (Matheny et al 1993). This modification made the model easier to accept by the prospective participants, therefore more feasible from a practical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using a non‐brushing model showed that application of CHX with a tray for 3 weeks allowing for experimental gingivitis to develop resulted in a significant reduction in plaque and gingivitis when comparing the specially formulated CHX dentifrice to a placebo . More recent work using a 3‐day non‐brushing model shows that 0.12% CHX dentifrice–gel applied in a tray did not differ on plaque accumulation as compared to a regular dentifrice .…”
Section: Discussionmentioning
confidence: 99%
“…It would be ideal to incorporate CHX in a dentifrice formulation as most patients daily use a dentifrice. The potential of this has been shown in a non‐brushing study where the use of CHX dentifrice resulted in significant less plaque and gingivitis as compared to the placebo . At present, a systematic evaluation has not yet been performed on the effect of toothbrushing with a CHX dentifrice or gel on clinical parameters of plaque and gingivitis, evaluating the side effects and tooth surface discoloration.…”
Section: Introductionmentioning
confidence: 99%
“…From its inception in 1965, 1,2 this model of inflammation has been used to assess how drugs,(3) bioactive compounds in dentifrices 4−6 and environmental toxins, such as tobacco smoke, 7,8 affect the development of inflammation. The model is designed to enable the study of both the induction and resolution of inflammation, which can also be assessed over a relatively short period of time (35 days) and in a controlled manner.…”
Section: Introductionmentioning
confidence: 99%